Black Garlic Improves Heart Function in Patients With Coronary Heart Disease by Improving Circulating Antioxidant Levels - Liu, Jingbo; Zhang, Guangwei; Cong, Xiaoqiang; Wen, Chengfei (Frontiers in Physiology, 2018)
Background: Black garlic (BG) has many health-promoting properties. Objectives: We aimed to explore the clinical effects of BG on chronic heart failure (CHF) in patients with coronary heart disease (CHD). Design: The main components of BG were measured by gas chromatography–mass spectrometry (GC–MS) and its antioxidant properties were determined by the clearance rate of free radicals. One hundred twenty CHF patients caused by CHD were randomly and evenly assigned into BG group and placebo group (CG). The duration of treatment was 6 months. Cardiac function was measured according to the New York Heart Association (NYHA) functional classification system. The following parameters were measured, including walking distance, BNP precursor N-terminal (Nt-proBNP), left-ventricular ejection fraction (LVEF) value, and the scores of quality of life (QOL). The circulating antioxidant levels were compared between two groups. Results: There are 27 main compounds in BG with strong antioxidant properties. BG treatment improved cardiac function when compared with controls (P < 0.05). The QOL scores and LVEF values were higher in the BG group than in the CG group while the concentration of Nt-proBNP was lower in the BG group than in the CG group (P < 0.05). Circulating antioxidant levels were higher in the BG group than in the CG group. Antioxidant levels had positive relation with QOL and LVEF values, and negative relation with Nt-proBNP values. Conclusion: BG improves the QOL, Nt-proBNP, and LVEF in CHF patient with CHD by increasing antioxidant levels.